Modern criteria for the design of corporate governance systems - Levanova, Lidiya N. (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право», 2022)
Introduction. Modern corporate governance systems of leading domestic corporations take into account, on average, slightly more than 50% of the requirements of the International Best Practices in Corporate Governance, which indicates their imperfection, low corporate reputation in the eyes of the investment community and undercapitalization in the domestic and foreign stock markets. This fact requires a more thorough approach to the design of corporate governance systems, taking into account not only established practices, Russian and international requirements for these systems, but also innovations that appear in the international principles of corporate governance of the OECD. Theoretical analysis. The article analyzes approaches to the process of designing corporate governance systems in Russian corporations, which consist in complying with updated international requirements for “good corporate governance”: long-term sustainable development of a company with a focus on stakeholders, taking into account ESG criteria. The author reveals the content of the design process, substantiates the possibility of using PhICS-modeling in this process. Empirical analysis. The work carried out an audit of the corporate governance system of a particular public corporation, on the basis of which its advantages and inconsistencies with the recommendations of the Corporate Governance Code were identifi ed. Results. In the process of research, the necessity of the designing corporate governance systems process of Russian corporations is substantiated. On the basis of a special organization, the application of modern criteria for designing a corporate governance system is shown, with the help of PhICS-modeling, directions for improving its quality are developed.